2014
DOI: 10.3324/haematol.2013.097154
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin-Cre reporter mice trace neutrophils, monocytes/macrophages and distinct subtypes of dendritic cells

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nhematopoiesis has revealed that HSCs express C/EBPα. 16To the best of our knowledge, there is no available mouse model for tracing myeloid cells without concurrent labeling of HSCs and lymphoid cells. Lactotransferrin (LTF, LF, CSP82) is well known as an iron-binding protein in the milk, saliva and mucosal secretions of the trachea, uterus and ovaries and has been implicated in innate immune responses against microbial infections.17,18 Ltf knockout mice have norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…MPO, LF, and elastase are known to be expressed at high levels by neutrophils, but literature suggests that they are also expressed at low levels in monocytes [25][26][27][28]. We confirmed these data on monocytes (Supplemental Fig.…”
Section: Activated Monocytes But Not Modcs Release Net-like Extracellsupporting
confidence: 86%
“…MPO, LF, and elastase are known to be expressed at high levels by neutrophils, but literature suggests that they are also expressed at low levels in monocytes [25][26][27][28]. We confirmed these data on monocytes (Supplemental Fig.…”
Section: Activated Monocytes But Not Modcs Release Net-like Extracellsupporting
confidence: 86%
“…Literature searches indicated that 14 of the top 25 proteins overexpressed in Pten ‐KO mouse prostate were associated with inflammation and/or immunity. Specifically, myeloid/neutrophil‐related innate immunity marker S100a8/calprotectin and Ltf/lactotransferrin (another myeloid lineage marker tracking neutrophils, monocytes/macrophages, and distinct subtypes of dendritic cells 17 ) stood out along with Reg3g, Pglyrp1, Lgals3, Pigr, Lcn2, Anxa1, Anxa3, and so forth. Other changes included glutathione conjugative metabolism (Gsto1 and Gsta4), proteases related to invasiveness, histones, and chromatin features related to enhanced cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mice expressing cre recombinase together with a diphtheria toxin or its receptor have been developed in order to trace or conditionally delete cells of a target lineage73. Gene loci encoding S100A8 7475, Lyz2 7677, Ltf 78, Elane 79, and Ly6g 80 have been used for targeting neutrophils, although some other types of myeloid cells are labeled to a certain degree. For example, monocytes and macrophages are also labeled in Lyz2 ( LysM ) -cre mice.…”
Section: Resultsmentioning
confidence: 99%